answersLogoWhite

0

One step you usually want to take is to move any perfect square out of the radical.

Example 1, with numbers: root(12) = root(4x3) = root(4) x root(3) = 2 root(3)

Example 2, with variables: root(y cubed) = root(y squared times y) = root(y squared) times root(y) = y root(y)

User Avatar

Wiki User

9y ago

Still curious? Ask our experts.

Chat with our AI personalities

ProfessorProfessor
I will give you the most educated answer.
Chat with Professor
RossRoss
Every question is just a happy little opportunity.
Chat with Ross
FranFran
I've made my fair share of mistakes, and if I can help you avoid a few, I'd sure like to try.
Chat with Fran

Add your answer:

Earn +20 pts
Q: How do you simplify the radical?
Write your answer...
Submit
Still have questions?
magnify glass
imp